BUXORO AMIRLIGINING MAHALLIY BOShQARUVI ORGANLARINING ShAKLLANIShI VA FAOLIYATI - Xakimov, J.N. (SCIENCE and SOCIETY, 2025)
This article provides an overview of the development of governance in the Bukhara Emirate and its components. It also shows how the governance reforms during the reign of Shohmurod advanced to a new stage. The Amir governed the state through officials, or the Amir's servants, who formed the administrative apparatus of the government. By the mid-18th century, the position of qushbegi had risen to a leading role, becoming the central component of the state apparatus and consolidating all major functions of governance in its hands. In the Emirate, one of the central institutions was a ministry responsible for defense and military affairs.
Keywords: Central Governance; Qushbegi; Said; paternity; chancellony; Shohmurod; Manghits; Religious Titles; Muhtasib; Mudarris